Effect of insect chitin as feed supplement in selected clinical biochemistry and growth performance of the broiler chickens - Juahari, Siti Nur Afiqah (2015)
A total of 36 twenty one day Ross broiler chicks were randomly allocated to 1 of 3 treatments in a study conducted to determine the effects of dietary supplementation of insect chitin (IC) on growth and blood composition. The experimental diets consisted of an unsupplemented basal control diet based on corn, soybean meal, and grain by-products, second treatment consisted of basal diet supplemented with 1 g IC/kg of diet, and third treatment consisted of 2 g IC/kg of diet. Each treatment was fed to 3 replicate pens of birds, with 4 birds per pen. Broiler performance and blood metabolite indices were measured at the beginning and every 7 day during the 21 day experimental period. Throughout the 21 day experimental period the control group broilers recorded the highest average daily gain (ADG) than the other treatments but the difference was not significant. There was no significant difference in ADG of broilers fed 2 g of IC than broilers fed 1 g of IC even though broilers supplemented with 2 g IC recorded higher ADG. The blood metabolite profiles for all treatment diets were similar. In conclusion, dietary supplementation of IC appeared not to improve ADG and blood metabolites of broilers. Poor responses of broilers to IC supplementation in this study was probably due to low quality IC product or the level of IC tested in this study was too low for the animal to respond.